Tlingit Indian wearing Chilkat blanket poses with masks and carvings, Alaska, ca. 1903 - Hegg, Eric A., 1867-1948
Man wears a carved and decorated headdress, Chilkat blanket around shoulders; stands on carved boxes surrounded by masks and carvings, ca. 1900-1905.